2022
DOI: 10.1007/s00406-022-01491-9
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of escitalopram in blood of patients treated in a naturalistic setting: focus on patients with alcohol and benzodiazepine use disorder

Abstract: The selective serotonin reuptake inhibitor escitalopram (ESC) is indicated for the treatment of major depressive disorder (MDD) and of generalized anxiety disorder (GAD). Monitoring of blood levels (BLs) is strongly indicated due to ESC’s high interindividual pharmacokinetic variability. The aim of this study was to analyse clinical efficacy and pharmacokinetic influences on ESC BLs, in patients with depressive disorder alone and with comorbid alcohol or benzodiazepine use disorder. Data were collected from pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
3
7
0
Order By: Relevance
“…The mean serum concentration and C/D ratio in our study were in line with previously reported findings [13,[19][20][21], although, higher than those indicated in the TDM guidelines [9]. In line with reporting of previous studies, we found increasing C/D ratios with age [2,21]. In our study, patients at the age 60 years and older have more than twice as high escitalopram concentrations compared to patients aged 30 years and younger (C/D ratios: 2.56 ± 1.47 vs. 1.06 ± 0.55).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The mean serum concentration and C/D ratio in our study were in line with previously reported findings [13,[19][20][21], although, higher than those indicated in the TDM guidelines [9]. In line with reporting of previous studies, we found increasing C/D ratios with age [2,21]. In our study, patients at the age 60 years and older have more than twice as high escitalopram concentrations compared to patients aged 30 years and younger (C/D ratios: 2.56 ± 1.47 vs. 1.06 ± 0.55).…”
Section: Discussionsupporting
confidence: 93%
“…We furthermore present an overview of escitalopram pharmacokinetics, in a sample of older-aged patients and patients being treated with several concomitant medications. The mean serum concentration and C/D ratio in our study were in line with previously reported findings 13 19 20 21 , although, higher than those indicated in the TDM guidelines 9 . In line with reporting of previous studies, we found increasing C/D ratios with age 2 21 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…65 In addition, 80% of SERT thresholds derived from PET studies are in line with lower efficacy concentrations reported for the drug that predict response to the treatment. [66][67][68] One study demonstrated that treatment response was related to pretreatment SERT binding ratios in the key regions of depression. 20 SNRIs are believed to exert their action by a combination of SERT and NET engagement with varying activities at both transporters, making it more complicated to determine a specific threshold.…”
Section: Discussion Gap Analysis and Outlookmentioning
confidence: 99%
“…65 In addition, 80% of SERT thresholds derived from PET studies are in line with lower efficacy concentrations reported for the drug that predict response to the treatment. 66–68 One study demonstrated that treatment response was related to pretreatment SERT binding ratios in the key regions of depression. 20…”
Section: Discussion Gap Analysis and Outlookmentioning
confidence: 99%